The Influence of Knowledge Management and Product Innovation on Sales in E-Commerce With Price as A Moderator - Kamaruddin, Muhammad Junaid; Darnis, Rahmi; Harisuddin (MJK PUBLISHER, 2025)
The aim of this research is to find out whether knowledge management and product innovation have an impact on e-commerce sales which is moderated by price. As a result of this research, we can gain a better understanding of how individuals with managerial skills can manage all e-commerce activities. We can also learn how they can innovate products by considering customer needs and wants, as well as how much they are willing to pay for the products they sell. The sample used in this research consisted of 100 respondents who came from various educational and community backgrounds. This research is quantitative research using the structural equation model analysis method. The aim of this research is to use high-quality data to show that knowledge management has a positive impact on e-commerce sales and product innovation.